The impact of international migration on the public pension system: the case of Portugal - Alves, J.; Craveiro, D.; Garcia, M. T. M.; Albuquerque, P. (International Social Security Review, 2019)
This article analyses the impact of replacement migration on the financial sustainability of the old-age pension system in Portugal, a country with one of the largest ageing populations in Europe. We do this using demographic forecasts and prospective exercises for the evolution of the Portuguese economy. During the 2015-2060 period, our results evidence the positive impacts of international migration on old-age pension system financial balances, reaching over 3 per cent of GDP after 2045. Moreover, even when taking into considering the low dynamics for the Portuguese economy, replacement migration is an important input to improve pension system financial sustainability.